Existence and multiplicity of solutions for nonlocal systems involving fractional Laplacian with non-differentiable terms. Issue 3 (17th February 2017) - Teng, Kaimin; Wu, Xian
Abstract : In this paper, we devote to the study of the existence and multiplicity of solutions of nonlocal systems involving fractional Laplacian with non-differentiable terms using some extended critical point theorems for locally Lipschitz function on product spaces.